2009
DOI: 10.1007/s12017-009-8090-1
|View full text |Cite
|
Sign up to set email alerts
|

Translin-Associated Factor X Gene (TSNAX) may be Associated with Female major Depressive Disorder in the Japanese Population

Abstract: Several investigations have reported that the translin-associated factor X gene (TSNAX)/disrupted-in-schizophrenia-1 gene (DISC1) was associated with major psychiatric disorders including schizophrenia, bipolar disorder (BP), and major depressive disorder (MDD). TSNAX is located immediately upstream of DISC1, and has been shown to undergo intergenic splicing with DISC1. It thus may also be influenced by translocation. To our knowledge, there are no reported gene-based association analyses between TSNAX and moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…These findings directly link translin to the pathophysiology of complex human neuropsychiatric disorders [83]. The TRAX gene has also been genetically linked to human psychological disorders, supporting the proposal that mRNA processing by translin/TRAX is important for brain function in humans [87][88][89][90][91][92].…”
Section: Regulation Of Mrna Dynamics: Key Roles In Germ Line Developmsupporting
confidence: 56%
“…These findings directly link translin to the pathophysiology of complex human neuropsychiatric disorders [83]. The TRAX gene has also been genetically linked to human psychological disorders, supporting the proposal that mRNA processing by translin/TRAX is important for brain function in humans [87][88][89][90][91][92].…”
Section: Regulation Of Mrna Dynamics: Key Roles In Germ Line Developmsupporting
confidence: 56%
“…This gene has been previously associated with MDD, acting as a regulator of neurodevelopment, neuroplasticity and neurotransmission (Okuda and others 2010). Besides that, several studies have reported associations of the GNPAT gene with neurological disorders in humans, especially with rhizomelic chondrodysplasia punctata (RCDP), a disorder of peroxisome metabolism resulting from a deficiency of plasminogen, a specialised class of membrane phospholipids, causing mental problems (Liu and others 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This scale is very well known for evaluation of depression. It has been translated into Japanese, is also validated for a Japanese version [8] and is widely used for detection of major depression disorders in Japanese patients [ 9 , 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%